'The Pursuit' of the imperfections in stop motion animation - Yeoh, Ree Yan (Nanyang Technological University, 2023)
This paper will document some of the challenges faced whilst exploring the ways in which stop motion animation supports the theme of the imperfections of the endless pursuit of excellence. Studying and discussing the psychology behind what influences audience engagement, how textures, frame rates, and the practical limitations of a school environment all play a part in conveying the theme of the endless pursuit of excellence, and how they all influence the final significance of the animation.